Characterization of Pickering emulsion gels stabilized by zein/gum arabic complex colloidal nanoparticles. (January 2018) - Dai, Lei; Sun, Cuixia; Wei, Yang; Mao, Like; Gao, Yanxiang
Abstract: Recently, Pickering emulsions have attracted extensive interests due to their advantages of "surfactant-free" and sustained delivery for bioactives. However, developing natural, biodegradable and food grade nanoparticles as Pickering emulsion stabilizers face new challenges. In this study, zein/gum arabic (GA) complex colloidal nanoparticles (ZGAPs) were prepared with a core-shell structure through hydrogen bonding and electrostatic interactions. The mean size of ZGAPs was larger than that of zein nanoparticles, and the zeta potential reversed from positive to negative, further confirming that GA molecules adsorbed onto the surface of zein nanoparticles. The three-phase contact angle ( θ o/w ) of zein nanoparticles was around 133.75°. After addition of GA, the θ o/w of ZGAPs was adjusted to 88.95° closing to neutral wettability. This result indicated that ZGAPs could be developed as effective Pickering emulsifiers. Confocal laser scanning microscope images evidenced that ZGAPs formed a densely packed layer at the surface of oil droplets, which provided compact barriers of the droplets against coalescence and Ostwald ripening. At constant particle concentrations, the oil volume fraction significantly influenced the droplet sizes and rheological properties of Pickering emulsions. The droplet size and emulsified phase volume fraction of Pickering emulsions were increased with the rise of oil fraction. Consequently, Pickering emulsion gels were successfully fabricated at a higher oil fraction φ ≥ 0.5, which exhibited a long-term storage stability. These findings would provide a potential way of producing Pickering emulsion gels, which showed the advantages of both emulsions and gels, and could become novel and effective delivery systems of bioactives. Graphical abstract: Highlights: Zein and GA complex nanoparticles (ZGAPS ) were fabricated as Pickering emulsifiers. ZGAPS were generated through hydrogen bonds and electrostatic interactions. The three-phase contact angle of ZGAPs was tuned to intermediate wettability. ZGAPS prepared Pickering emulsion gels exhibited a long-term storage stability. ZGAPs formed a densely packed layer at the surface of oil droplets.